ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP AUDIT REPORT LAG - Armania Putri Wardhani; Surya Raharja (Diponegoro Journal of Accounting, 2013)
This study aims to examine and analyze the effect of the size of the audit committee, audit committee independence, audit committee meeting, Competence Audit Committee Member, Board Size, and Independent Commissioner of the audit report lag on all the companies listed on the Indonesia Stock Exchange in 2010-2011. This study is an empirical study with purposive sampling technique in data collection. Secondary data obtained from the financial annual report of 412 companies listed on the Stock Exchange in 2010-2011. Data analysis was performed by multiple regression. The results of hypothesis testing indicated that audit committee independence, competency audit committee members and board size significantly influence the audit report lag. Furthermore, the size of the committee, audit committee meeting, the Independent Commissioner no significant effect on audit report lag.